The Use of Students’ Feedback for Effective Learning in Engineering Units - Anwar, Faisal (Common Ground Publishing, 2012)
This paper demonstrates the use of online survey data of students’ feedback in two civil engineeringunits (one undergraduate-Water Engineering 361 and one postgraduate-EnvironmentalEngineering Management 690) at Curtin University, Western Australia and shows how it enhancesthe overall learning outcomes. The students’ feedback are collected for these units for two consecutiveyears using a university-wide online survey system known as “eVALUate”-an evaluation instrumentfor measuring students’ perceptions of their engagements and learning outcomes. In the first year ofteaching these units, traditional method of teaching was used and the overall students’ satisfactionand the learning outcomes were found below the university or faculty agreement. All the suggestionsand criticisms in eVALUate from the 1st year of teaching were taken into consideration for redesigningthese units. A new blended teaching approach composed of traditional and e-learning system basedon the students’ feedback was formulated and adopted. The eVALUate survey data in the 2nd year ofteaching shows that the learning outcomes and the overall students’ satisfaction exceed the target ofuniversity and faculty agreement. The survey results indicate that the blended teaching approach basedon students’ feedback provides better learning outcomes in engineering units.